Nanofiber PVA/ZnO Sebagai Material Antimikroba Pada Wound Dressings - putri uzalia; diah hari kusumawati (Jurnal Teori dan Aplikasi Fisika, 2023)
Nanofibers are ideal for forming multifunctional medical products, one of which is wound dressings. Nanofibers wound dressings made from polyvynyl alcohol (PVA) and zinc oxide (ZnO) using the electrospinning method with varying voltages of 15 kv, 16 kv, 18 kv, and 20 kv, to determine the effect of stress on morphology, absorption and antibacterial activity. The resulting nanofibers have a smooth surface and an almost uniform fiber diameter. SEM analysis showed that the diameter of PVA 10% with a magnification of 50000X was 252 nm and PVA/ZnO 20 kv with a magnification of 30000X was obtained 231 nm, the EDX spectrum contained elements of C, O, and Zn respectively 37.40%, 62.14%, and 0.46%. The results of the FTIR analysis showed that the functional groups seen in the PVA/ZnO samples were O-H, CH2, C-H, C-O, and Zn-O. UV-Vis transmission showed that PVA had a high UV transmission of 12% but all PVA/ZnO nanofibers showed a UV transmission of almost 0%. Antimicrobial activity showed that the number of bacterial colonies in PVA/ZnO samples was less than the control. The average nanofibers diameter increases when ZnO nanoparticles are added, but when tension is increased, the average diameter of the nanofibers decreases. The morphology of the nanofibers is very uniform and there are no ZnO nanoparticle crystals, so PVA/ZnO nanofibers can be chosen as an ideal biomaterial for wound dressings.